Identification with School and Head Trauma: Parental Perceptions on Student’s Experiences - BreAnna Jones; Lindsay Robinson; Karen H Larwin (International Journal of Evaluation and Research in Education (IJERE), 2015)
In the United States 40% of all traumatic brain injuries (TBI) are in children under the age 14 (Broque  et. al 2012). This means a portion of the school age population is exposed to head injury every year. The effect this injury and experience can have on a child varies, but it is important for educators, counselors, and family to understand the psychosocial experiences that follow after TBI. Research has shown that head injury in childhood can have severe psychosocial effects if the injury is not treated, recognized, and planned for (Broque et. al 2012).This research is intended to shed light on what educators, counselors, and families can do to help children who have experienced a TBI. Previous research shows that a loss of sense of self after TBI in three categories; loss of self-knowledge, loss of self by comparison, and loss of self in the eyes of others (Nochi, 1998). This investigation suggests that identification as “disabled” can impact how students identify with their school.